Overcoming Barriers to Cervical Screening Among Pacific Women: A Narrative Review - McPherson, GS; Fairbairn-Dunlop, P; Payne, D (Mary Ann Liebert, 2019)
Purpose: This narrative review explores the barriers and facilitators for Pacific women accessing the cervical screening pathway. Despite organized cervical screening in New Zealand, Pacific women still face significant health disparities in regard to cervical cancer incidence and mortality and access to colposcopy services. Providing a narrative synthesis of the available literature examining Pacific women and the barriers and facilitators to the cervical screening pathway may provide some insight into the provision of primary and secondary health services for Pacific women. Methods: Four electronic databases were searched for articles published between January 1990 and June 2017 and included bibliographies of key journal articles and gray material. A narrative review and synthesis were undertaken of qualitative, quantitative, and mixed methods research. Results: The literature is focused on the cervical screening aspect of the cervical screening pathway. There was a paucity of literature that examines the barriers and facilitators Pacific women experience accessing colposcopy services. Barriers to cervical screening for Pacific women are multifaceted and interrelated. Factors such as culture, fear, practical issues, health care experiences, and knowledge/education influence screening practices. Facilitators to cervical screening are also multifaceted and included knowledge, health care experience, culture, and practical issues. Culturally tailored approaches improve access to cervical screening for Pacific women. Conclusion: Understanding Pacific women's experiences, facilitators, and barriers to the cervical screening pathway is essential in assisting health care professionals, policy makers, and funders provide culturally appropriate services. Further research is required to examine Pacific women's experiences of navigating colposcopy services and the interface between primary and secondary care services.
Keywords: Barriers; Cervical screening; Colposcopy; Facilitators; Pacific women